PUBLIC SPACES AS A SHOWCASE OF URBAN CULTURAL LANDSCAPE: A CONCEPTUAL FRAMEWORK FOR RECOGNIZING SUSTAINABLE ARCHITECTURE AS A TOOL FOR CREATING URBAN PUBLIC SPACES - AR. Iftikhar Ali; AR. Mir Wali Shah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The cityscape is a social construct that relies on an understanding and interpretation of the ManLandscape interaction since it develops and defines the cultural bond. We will be able to change the underlying characteristics of urbanization once we understand this cultural linkage. The main aim of this paper is to explore how urban open spaces needed to be seen and experienced as a unit to contain social processes under the cultural and environmental influence of a given location. These spaces give a spatial arena in which to act, feel, and experience behaviors. The architectural quality of public space is defined and influenced by the proper understanding of the symbolic and visual features of a specific public space in a locale. Architecture can be defined as an art that, with a specific function, defines and organizes spatial units in terms of actual spatial relationships inherent in people's social identity and culture. Secondly, urban open spaces arrangement represents culture and civilization, as well as our aspirations, goals, and concerns. Along with all of this, the aesthetic quality of the architectural environment, which is very creative, imagined, conceptual, and artistic, with various symbolic connotations, is an important component of it. This article provides the theoretical construct of the role that architecture and public spaces can play in generating a visual image in the minds of users for a certain built environment, such as a town or city. The outcomes of this study imply that cultural impressions are consistent in all populated places around the world and that each city is distinct in how it has responded to diverse environmental, cultural, and traditional provisions. This work emphasized the necessity to re-establish the importance of open public spaces, their values in current urban planning, and their revival in this work.